(untitled) (Fiep Bulletin - online, 2012)
This is the report of the experience of the discipline Epidemiology and Nursing, offered in the third period of an undergraduate degree in nursing from the State University of Rio Grande do Norte, in view of socializing political and pedagogical strategies that make explicit the commitment to train at the Institution with the consolidation of SUS outlined by the Brazilian Sanitary Reform Movement. Takes the challenge of shaping the foundations for building conception of epidemiology as a social practice and its methodological orientation of the Theory of Praxis Intervention in Public Health Nursing (TIPESC). We found that, in general, the experience was significant for the socialization of knowledge and practices among the actors, as well as to the qualification of health services, translating into a teaching / learning process consistent with reality. This process allowed the transformation of reality into problems identified in the content to be built. Thus meant the movement around the break with the biological, medicalized and hospital-centered paradigm and that shapes the organization of practices and education of health professionals. Significantly, the possibility of a viable formation consistent with the current health policy, for better integration of professionals in this space. We apprehend that SUS has taken a more active role in the reorientation of strategies and ways of teaching / learning of the discipline that is based on sustaining the rich debate between training institutions and the network of health services. This intention can not be considered as an act eminently technical. It is a political action since it involves changes in the relationships established, in the processes, practices in health and the actors involved and requires an intra and intersectoral coordination.